(untitled) (Gilgameš, 2016)
Il campo 29 is the debut as novelist of Sergio Antonielli. It was published in Milan in 1949 by “Edizioni Europee” and in 1976 by “Editori Riuniti”. The novel tells the personal experience of imprisonment in British Raj during the Second World War with other ten thousand Italian officers. Through the analysis of the text and documents from the archives of the author, stored in the Centro Apice, I would like to discuss the techniques of composition that make this work a peculiar case in the post-world war literary system. Antonielli, forcing himself to overcome the tragedy suffered, commits to the writing a dual purpose: to avoid mere “documentarismo” without overindulging in the romance, and to take the advantage of the exceptional nature of his experience to create a work that exceed all individual and historical contingencies. In respect of these moral and stylistic imperatives, the writer refuses the autobiography and choices a choral intonation, different from sentimental style, typical of other writers involved in the literature of war. His critic studies and the introductions, written by author for two editions, show distinct interpretations about his work and about typical methods and category of neorealist literature: document, diary, autobiographical novel. The story does not give way to political disquisitions or to sentimental parenthesis, but it consists of representation of the life in prison camps. A “city of prisoners” comes alive, where coexist vices and virtues of the normal society, and where the war is banned.